FLCCR is a fluorescent reporter system that quantifies the duration of different cell cycle phases at the single-cell level in fission yeast. - Guillem Murciano-Julià; Marina Francos-Cárdenas; Clàudia Salat-Canela; Elena Hidalgo; José Ayté (PLoS Biology)
Fission yeast is an excellent model system that has been widely used to study the mechanism that control cell cycle progression. However, there is a lack of tools that allow to measure with high precision the duration of the different phases of the cell cycle in individual cells. To circumvent this problem, we have developed a fluorescent reporter that allows the quantification of the different phases of the cell cycle at the single-cell level in most genetic backgrounds. To prove the accuracy of this fluorescent reporter, we have tested the reporter in strains known to have a delay in the G1/S or G2/M transitions, confirming the strength and versatility of the system. An advantage of this reporter is that it eliminates the need for culture synchronization, avoiding stressing the cells. Using this reporter, we show that unperturbed cells lacking Sty1 have a standard cell cycle length and distribution and that the extended length of these cells is due to their increased cell growth rate but not to alterations in their cell cycle progression.